Transformational Leadership Based in Sanghahavttu 4 of School Administrators in Extended Opporyunity Schools Under The Nakhon Sawan Primary Educational Service Area Office 1: - - Pho-ong, Narudee; Metheevachatra, Anond; Uttaro, Phramaha Udorn (Mahachula Academic Journal, 2026)
Abstract This research aimed to : (1) study the level of transformational leadership of administrators in opportunity expansion schools; (2) develop guidelines for transformational leadership based on the Four Sangahavatthu principles; and (3) evaluate the developed guidelines. The study used a mixed-methods design in three phases. Phase 1 collected data from 223 administrators and teachers using a questionnaire with a reliability value of 0.99, and analyzed the data using percentage, mean, and standard deviation. Phase 2 developed the guidelines through a focus group discussion with nine key informants and content analysis. Phase 3 evaluated the guidelines with 15 recognized school administrators under the Nakhon Sawan Primary Educational Service Area Office 1 using an evaluation form, and analyzed the data using mean and standard deviation. The findings revealed that (1) The overall level of transformational leadership of administrators in opportunity expansion schools under the Nakhon Sawan Primary Educational Service Area Office 1 was at the highest level. When considered by aspect, the aspect with the highest mean was communication and participation, which was at the highest level, followed by creating a shared vision and organizational commitment, also at the highest level. The aspect with the lowest mean was idealized influence, which was likewise at the highest level. (2) The guidelines for developing transformational leadership based on the Four Sangahavatthu principles among administrators in opportunity expansion schools consisted of six aspects, with four guidelines for each aspect according to the Four Sangahavatthu principles, totaling 24 guidelines.(3) The evaluation results of the guidelines for developing transformational leadership based on the Four Sangahavatthu principles among administrators in opportunity expansion schools showed that, overall, the aspects of accuracy, suitability, feasibility, and usefulness were all at the highest level. Keywords:Transformational Leadership;The Four Sangahavatthu principles; Administrators in Extended Opporyunity Schools